2019
DOI: 10.1186/s12917-019-1841-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and visual detection of Lawsonia intracellularis with an improved recombinase polymerase amplification assay combined with a lateral flow dipstick

Abstract: BackgroundLawsonia intracellularis (L. intracellularis) is the etiologic agent of porcine proliferative enteropathy (PPE), which is reported in many swine breeding countries all over the world, and has caused enormous economic losses in intensive pig production systems. Therefore, the aim of this study was to develop a simple and rapid method for on-site detection of Lawsonia intracellularis (L. intracellularis). As the isothermal recombinase polymerase amplification (RPA) can be performed at a constant temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The detection rate of RPA-LF-GPS is 98.1% (51/52), and that of PCR is 90.4% (47/52). Statistic analysis showed that RPA-LF-GPS and PCR had equal sensitivity ( P > 0.05), which is consistent with previous reports about RPA [29]. This result showed that the RPA-LF-GPS performed well with clinic samples, which make it a potential to replace PCR.…”
Section: Discussionsupporting
confidence: 89%
“…The detection rate of RPA-LF-GPS is 98.1% (51/52), and that of PCR is 90.4% (47/52). Statistic analysis showed that RPA-LF-GPS and PCR had equal sensitivity ( P > 0.05), which is consistent with previous reports about RPA [29]. This result showed that the RPA-LF-GPS performed well with clinic samples, which make it a potential to replace PCR.…”
Section: Discussionsupporting
confidence: 89%
“…Magnetic bead-based extraction methods will be used in future research to prepare the RPA templates from clinical samples. Extraction using magnetic beads is easy and time-saving, and it does not require potentially dangerous procedures or specialized laboratory equipment [ 26 , 27 ]. The combination of the RT-RPA-VF assay with magnetic bead-based nucleic acid extraction techniques represents a very promising point-of-care detection method.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). 50 , 62 , 64 , 81 , 97 , 99 , 111 Pigs experimentally infected with L. intracellularis are expected to show L. intracellularis shedding in feces by 7 dpi and may sustain shedding of the bacterium for up to 10 wk after infection ( Fig. 2B ).…”
Section: Molecular Detectionmentioning
confidence: 99%
“… 31 , 96 The gene target commonly used is the 16S ribosomal DNA gene (16S rDNA), 64 although aspA 99 and dnaA 111 have also been used as markers for L. intracellularis . 42 , 64 , 111 Various primer pairs have been used for detection of L. intracellularis ( Table 2 ). “In situ” amplification in tissue samples has also been reported and could potentially be a good candidate to substitute for tissue IHC.…”
Section: Molecular Detectionmentioning
confidence: 99%